MOLECULAR DETECTION of INFECTIOUS PATHOGENS of the UPPER RESPIRATORY TRACT in CAPTIVE NONDOMESTIC FELIDS - Lara, Valeria M.; Benassi, Julia C.; Bisetto, Shayne P.; De Oliveira, Trícia M.; Ferreira, Helena L.; Araújo, Joao P. [UNESP]; Carregaro, Adriano B. (American Association of Zoo Veterinarians, 2017)
Upper respiratory tract disease is a complex infectious disease process with multiple pathogens involved. Identification of infectious agents in wild animals is of great importance for wildlife conservation. The aim of this study was to evaluate the molecular detection of feline herpesvirus type 1, feline calicivirus (FCV), Bordetella bronchiseptica, Chlamydophila felis, and Mycoplasma felis using ocular and nasal swabs in three species of captive nondomestic felids. Mycoplasma felis was detected in two ocular samples of Puma concolor and in one nasal sample of one Panthera onca. FCV was detected in association with M. felis in one P. concolor. The other pathogens tested were not detected. To the authors' knowledge, this is the first report of M. felis in nondomestic felids from Brazil.
Keywords: FCV; FeHV-1; Mycoplasma felis; nondomestic cats; respiratory infection